Eruptions and Social Media: Communication and Public Outreach About Volcanoes and Volcanic Activity in Italy - Todesco, Micol; De Lucia, Maddalena; Bagnato, Emanuela; Behncke, Boris; Bonforte, Alessandro; De Astis, Gianfilippo; Giammanco, Salvatore; Grassa, Fausto; Neri, Marco; Scarlato, Piergiorgio; Neri, Augusto (Frontiers in Earth Science, 2022)
Italy is the land of iconic volcanoes, whose activity has been witnessed, described and portrayed for centuries. This legacy has greatly contributed to shaping the public perception of volcanoes and their impact, well beyond the national borders. Stories about famous eruptions overlap and nowadays easily mix up with the impressive footage that is readily available from ongoing eruptions worldwide. As a result, the wide spectrum of possible phenomena may be flattened into an oversimplified sketch of volcanic eruptions and their impact. Actual volcanoes differ in size, eruption magnitude, state of activity, eruptive style and geographical position, not to mention the human environment. All these elements combine in defining the consequences of volcanic activity as well as in determining the severity of the damage and the size of the impacted area. An effective hazard communication should therefore reflect the complexity of real volcanic settings and provide adequate tools and information to recognize and understand the specific features of each volcanic area. Focusing on Italy, as we write, two Italian volcanoes (Stromboli and Etna) display persistent eruptive activity, while other two are going through unrest phases that started in 2012, at Campi Flegrei, and in late summer of 2021, at Vulcano Island. The other active volcanoes, including Vesuvius, Colli Albani, and the islands of Ischia, Lipari, and Pantelleria have been dormant for tens, hundreds, or thousands of years. Here we discuss the online communication strategies implemented by the Istituto Nazionale di Geofisica e Vulcanologia (INGV) since 2018 to inform Internet and social media users about volcanoes, volcanology, and ongoing volcanic activity, both in Italy and abroad. We describe the internal procedures that we developed and practiced and the experience gathered so far, during both quiet periods and a few volcanic crises that occurred in recent years and required an important communication effort.